2017
DOI: 10.12913/22998624/66505
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Energy Consumption by Passenger Car With Using of Non-Electrical Hybrid Drive Technology

Abstract: Not only electrical hybrid technology is used for drivetrain of passenger cars. Also other systems using non-electrical principles (hydraulic or air pressure, mechanical energy storage) can be found in modern vehicles. There is a quantification of the spared energy by using a hybrid vehicle in the paper. Driving cycle ECE 15 was chosen as a platform for simulation of driving resistances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Practical applications of the procedures described above are shown in this section on the example of univariate statistical analysis of maintenance efficiency economic issues of the vehicle fleet of Lublin Regional Branch of the Polish Post Logistics Centre (RB PPLC). The functioning of the national postal operators in the new EU countries is subject to various analyses [1,21,22,24,27,37,38].…”
Section: Sample Analysismentioning
confidence: 99%
“…Practical applications of the procedures described above are shown in this section on the example of univariate statistical analysis of maintenance efficiency economic issues of the vehicle fleet of Lublin Regional Branch of the Polish Post Logistics Centre (RB PPLC). The functioning of the national postal operators in the new EU countries is subject to various analyses [1,21,22,24,27,37,38].…”
Section: Sample Analysismentioning
confidence: 99%
“…Scientists from Canada and Slovakia observed that HEV are 26-28% more fuel efficient than gasoline vehicles [15,16]. However, the fuel efficiency of HEVs is more sensitive to changes in ambient temperature.…”
Section: Comparison Of Conventional and Hybrid Cars Exploitation Costsmentioning
confidence: 99%
“…The reduction of oil sources, the increase of environment pollution and the intensification of climate changes have led the whole world looking for alternative fossil energy sources for more efficient usage [1]. Energy intensity of transport is a current topic around the world [2]. At present, the drives of vehicles use energy that is largely bounded in fossil fuels [3,4].…”
Section: Introductionmentioning
confidence: 99%